Um estudo exploratório sobre o nível de aderência em empresas, com atuação no Brasil, às normas e recomendações de organismos nacionais e internacionais relativas à divulgação de informações de natureza ambiental - Lindstaedt, Ângela Rozane de Souza (Universidade do Vale do Rio do Sinos, 2007)
With the growing worldwide interest and awareness of organizations and government organs that have an important role in the area of sustainable development, various standards and recommendations for environmental information disclosure are being issued. Some international entities connected to accounting, such as the Intergovernmental Working Group of Experts on International Standards of Accounting and Reporting (ISAR/UNCTAD) and the International Federation of Accountants (IFAC), have turned their attention to accounting information that relates to environmental sustainability. In the same way, in United States of America and Brazil some entities have issued standards for account recording and publication of environmental information. These standards relate both to identification and environmental nature information reporting in annual corporate reports. In this context, this exploratory study seeks to evaluate the degree of conformance of a sample of 10 (ten) companies in chemical and petrochemical sector,
Keywords: normas ambientais; segmento químico e petroquímico; evidenciação; chemical and petrochemical Sector; environmental regulamentation; disclosure; Ciências Sociais Aplicadas